IKLIM KOMUNIKASI ORGANISASI DI PT. RIAU MEDIA TELEVISI PEKANBARU - Yosua Siahaan; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
PT. Riau Media Television Pekanbaru is the first local television station in RiauProvince. In order to make this television station become the best one, is not just theresponsibility of the leader, but also the subordinates. The objectives of this study were todetermine the interaction of communication, work culture, and communication barriers inclimate organizational communication that occurred in PT. Riau Media Television Pekanbaru.This study had been conducted from March - April 2015 in PT. Riau Media TelevisionPekanbaru. This study used descriptive qualitative research method with data collectiontechniques of observation, interviews and documentation. The object of this study is ClimateOrganizational Communication of PT. Riau Media Television Pekanbaru with subjects thataccomplished the research needs which as many as 8 people consisting of 5 leaders and threeemployees of PT. Riau Media Television Pekanbaru.Results showed that the interaction of communication that occurs in PT. Riau MediaTelevision Pekanbaru was running smoothly enough and opened. It can be seen in the downwardcommunication, upward communication and communication among the fellow employees. Wherecommunications are made to create a conducive atmosphere and effective communication inorder for the implementation of maximum performance for corporate purposes. Meanwhile thework culture that occurs in PT. Riau Media Television Pekanbaru form a consistency in applyingdiscipline in every action, enforcement of rules, and policies will encourage the emergence ofconditions of openness, full disclosure situation will improve horizontal and verticalcommunication, personal relationships between the formal and informal levels of management,so the growing attitude mutual respect. The communication barriers in Climate OrganizationalCommunication PT. Riau Media Television Pekanbaru are the interest in responding to or live amessage that would make an employee being selective and only pay attention to the stimuliassociated with their interest, hidden motivation that encourages employees to do something inaccordance with the wishes, needs and shortcomings it has, and their prejudices raises emotionsforcing employees to draw conclusions on the basis of prejudice without using a rational mind.Keyword: Climate Organizational Communications, Interaction Of Communication,The Work Culture, The Communication Barriers